Capital inflow surges and consequences - Atish R. Ghosh; Mahvash Saeed Qureshi (Asian Development Bank Institute (ADBI), 2016)
While capital flows to emerging markets bring numerous benefits, they are also known to create macroeconomic imbalances (economic overheating, currency overvaluation) and increase financial vulnerabilities (domestic credit growth, bank leverage, foreign currency-denominated lending). But are all inflows the same? In this paper, we examine whether the source of the inflow - residents repatriating foreign assets or nonresidents investing in the country - or the type of inflow (foreign direct investment, portfolio, other investment, etc.) makes any difference to the consequences of the capital flow. Our results, based on a sample of 53 emerging markets over 1980 - 2013, show that when it comes to the source of the inflow, the macroeconomic and financial stability consequences of flows driven by residents (asset flows) and nonresidents (liability flows) are broadly similar in economic terms. Formal statistical tests, however, suggest that liability flows are more prone to causing economic overheating and domestic credit expansion than asset flows. On the types of inflows, we find that compared to direct investment, portfolio debt and other investment flows are associated with larger macroeconomic imbalances and financial vulnerabilities. We conclude that policy should try to mitigate the untoward consequences of inflows, and shift their composition from risky to safer forms of liabilities.
Keywords: F21; F32; F38; F41; F42; F62; 330; capital flow; emerging markets; macroeconomics; economic overheating; credit expansion; currency; overvaluation; domestic credit; bank leverage; foreign currency; lending; FDI; foreign direct investment; investment; financial stability; asset flow; liability flow; portfolio debt